Monitoring the the Impacts of Climate Change and Variability on the Phenology of Natural Vegetation Using 250m MODIS-NDVI Satellite Data: Cace Study of the Dryland Ecosystem of Sokoto, North-Westrn Nigeria. - Abubakar Magaji Jibrillah; Garba Abdulmumin Budah; Dalhatu Ahmad; Nathanial Bayode Eniolorunda (Faculty of Geography, Universitas Gadjah Mada, 2023)
Recent climate change and variability together with other anthropogenic drivers have exerted tremendous pressure on the fragile dryland ecosystem of Sokoto, North-western Nigeria. Vegetation phenology is one of the active indicators of the impacts of climate change on the ecosystem. This study aimed to monitor how the ecosystem of the area responds to the challenges associated with climate change in order to provide baseline information for policies and programmes geared towards addressing these challenges. It explored the applications of remote sensing data (MODIS-NDVI), GIS and statistical analyses in achieving this aim. Image processing operations such as data extraction, raster calculations, geometric transformations and creation of the region of interest were conducted using ArcGIS 10.5 model builder while TIMESAT software was used determined the vegetation phenological events such as the start, end and length of the growing seasons. The results indicated a persistent decline in the length of the growing seasons of the major vegetation classes in the area due to late onset and early cessation of the growing season which is positively correlated with rainfall distribution. From the year 2001 to 2016, 36% and 33% declined in the length of the growing season were recorded for shrubs and grasses respectively. These are positively correlated with the annual rainfall distributions in the area, with the correlation coefficient of r = 0.40 and r = 0.36 for the shrubs and grasses respectively. Implications of these on the ecosystem and livelihoods of the people in the area were discussed and ways forward suggested.